Identity in Contemporary Malaysian Literature: Diversities, Writers’ Dilemma and Implications for Teaching - Collin, Jerome; Ting, Su Hie; Ruzy Suliza, Hashim (The Asian Journal of English Language & Pedagogy, 2016)
This article examines the construction of diverse identities in contemporary Malaysian literature. Using one literary text, “Neighbours” by Karim Raslan (1996), the analysis shows that the characters, particularly the ancillary male character, Kassim, possesses diverse identities with ethnic identity being foregrounded over other forms of identity that are based on age, social class, gender and sexuality. However, these other forms of identity exert influence over the realization of the characters’ ethnic identity, thereby reinforcing the idea that social identities do not exist in isolation, but interact with each other in the process of identity formation and expression. This article also discusses the dilemmas and challenges that local writers face in constructing the identities of their characters and their own identities in the process, as well as the implications of using the writers’ works to discuss issues related to identity in the literature classroom.